1996
DOI: 10.1063/1.362998
|View full text |Cite
|
Sign up to set email alerts
|

Comparative study on dry oxidation of heteroepitaxial Si1−xGex and Si1−xyGexCy on Si(100)+

Abstract: The goal of this study is to investigate the effect of carbon incorporation upon thermal oxidation of Si1−xGex alloys and its role on strain compensation in Si1−xGex alloys. Si1−xGex and Si1−x−yGexCy alloys on Si(100) are grown by combined ion and molecular beam deposition and are then oxidized at 1000 °C in a dry oxygen ambient for two h. The thickness and the composition of all samples before and after oxidation are measured by Rutherford backscattering spectrometry (RBS) combined with ion channeling at 2.0 … Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
3
1

Citation Types

0
10
0

Year Published

1997
1997
2011
2011

Publication Types

Select...
7
1

Relationship

0
8

Authors

Journals

citations
Cited by 23 publications
(10 citation statements)
references
References 17 publications
0
10
0
Order By: Relevance
“…This observation is in agreement with studies of the thermal stability of strained Si 1Ϫy C y layers. [5][6][7] Thus, the SIMS and TEM investigations published by Xiang et al 3 on samples at 1000°C are not realistic for practical reasons. Preliminary electrical studies of the oxides showed rather bad electrical quality.…”
Section: Discussionmentioning
confidence: 95%
See 1 more Smart Citation
“…This observation is in agreement with studies of the thermal stability of strained Si 1Ϫy C y layers. [5][6][7] Thus, the SIMS and TEM investigations published by Xiang et al 3 on samples at 1000°C are not realistic for practical reasons. Preliminary electrical studies of the oxides showed rather bad electrical quality.…”
Section: Discussionmentioning
confidence: 95%
“…Xiang et al have presented first results for dry oxidation of Si 1ϪxϪy Ge x C y /Si structures. 3 They investigated dry oxides grown at 1000°C. Jaquez et al studied the copper enhanced oxidation of Si 1ϪxϪy Ge x C y .…”
Section: Introductionmentioning
confidence: 99%
“…Making a complete list of the publications on the oxidation of Si x Ge 1Ϫx is beyond the scope of the present article. Most of the oxidation work has been carried out at atmospheric pressure but at elevated temperatures, either in a diffusion furnace ͑the conventional thermal oxidation͒ [6][7][8][9][10][11][12][13] or in dedicated equipment able to rapidly vary the substrate temperature ͑rapid thermal oxidation͒. 14 The oxidation can be made in O 2 ͑dry͒ 7,10,13 or H 2 O ͑wet͒ [6][7][8][9][10][11][12]14 atmosphere.…”
Section: Introductionmentioning
confidence: 99%
“…11 The most frequently used starting materials for the oxidation studies are Si x Ge 1Ϫx films with desired compositions. The films can be deposited with a variety of techniques such as chemical vapor deposition ͑CVD͒, 7,12,15 molecular beam ep-itaxy ͑MBE͒ [8][9][10]13,14,[16][17][18] and evaporation. 9,11 In addition to Si x Ge 1Ϫx films, silicon ion implanted with germanium can be utilized.…”
Section: Introductionmentioning
confidence: 99%
“…7 The dry thermal oxidation behavior of strained SiGe layer is dependent on oxidation temperature, Ge fraction, and ambient. [8][9][10] When a strained Si 1Ϫx Ge x layer with Ge content ͑xϽ0.5͒ is oxidized at high temperature ͑TϾ700°C͒, due to the large difference between the heat of formation of SiO 2 and GeO 2 , SiO 2 is more preferentially produced than GeO 2 . As a result, the thermally grown oxide is nearly pure SiO 2 , and Ge is rejected from the oxide and piled up below the oxide layer.…”
mentioning
confidence: 99%